2022
DOI: 10.1177/00315125221087025
|View full text |Cite
|
Sign up to set email alerts
|

Do Perfectionism Traits Predict Team Cohesion and Group Conflict Among Youth Athletes?

Abstract: In this cross-sectional study, we investigated the predictive power of perfectionism on 413 Brazilian athletes’ perceptions of team cohesion and conflict. Participants responded to the Sport Multidimensional Perfectionism Scale-2, the Youth Sport Environment Questionnaire, and the Group Conflict Questionnaire. In data analysis, we used Pearson correlations, multiple regression, latent profile analysis (LPA), and multiple analysis of variance. Regression analysis revealed that perfectionistic standards were pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
(119 reference statements)
1
2
0
Order By: Relevance
“…There were some interesting gender-related findings. In the present study, regarding socially prescribed and other-oriented forms of perfectionism, there were no significant differences between boys and girls, which is consistent with prior research conducted in other performance contexts (e.g., school) [17,62,63]. These findings are also consistent with those of previous studies that report differences between boys and girls in non-competitive, nonsports samples [21,22,64].…”
Section: Discussionsupporting
confidence: 92%
“…There were some interesting gender-related findings. In the present study, regarding socially prescribed and other-oriented forms of perfectionism, there were no significant differences between boys and girls, which is consistent with prior research conducted in other performance contexts (e.g., school) [17,62,63]. These findings are also consistent with those of previous studies that report differences between boys and girls in non-competitive, nonsports samples [21,22,64].…”
Section: Discussionsupporting
confidence: 92%
“…Perfectionism has been extensively studied in several fields, including sports, and in relation to various positive and negative psychological outcomes. For instance, studies have found that adaptive perfectionism is negatively related with negative outcomes, such as anxiety, negative affect, intentions to dropout or burnout, and positively related to sport performance, motivation, enjoyment, or team cohesion while negative dimensions of perfectionism show the opposite pattern (e.g., Mallinson-Howard et al, 2019 ; Deck et al, 2020 ; Freire et al, 2022 ; Olsson et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Flett and Hewitt (2005), developed the Multidimensional Perfectionism Scale (MPS), that measures self-oriented perfectionism, other-oriented perfectionism, and socially prescribed perfectionism, aligning with Frost's multidimensional model. They found that athletes with high levels of perfectionism, particularly self-oriented and socially prescribed perfectionism, are more prone to experience negative psychological outcomes such as anxiety, depression, burnout, and disordered eating (Freire et al, 2022;Olmedilla et al, 2022), while adaptive perfectionism can be associated with positive outcomes such as high achievement motivation and dedication (Flett & Hewitt, 2014).…”
Section: Introductionmentioning
confidence: 99%